Section 1.3 Exponents
Section Objectives
Understand exponents as a way of writing repeated multiplication in the same way multiplication represents repeated addition.
Develop fundamental properties of exponents through examples.
Develop the definition of zero, negative, and fractional exponents formally as consequences of fundamental exponent properties.
Most fundamentally, exponents represent repeated multiplication in the way that multiplication represents repeated addition.
Multiplication is to Addition as Exponents are to Multiplication
Multiplication as Repeated Addition | Exponents as Repeated Multiplication | |
---|---|---|
\(na = \underbrace{a+ a +\cdots + a}_\text{$n$ times}\) | \(\longrightarrow\) | \(a^n = \underbrace{a\cdot a \cdot\cdots \cdot a}_\text{$n$ times}\) |
Based on this idea, we can see the following properties of exponents:
Fundamental Properties 1.3.2. Properties of Exponents:.
\(a^na^m = a^{n+m}\text{.}\) For example: \(2^{3}\cdot 2^4 = 2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2\cdot 2 = 2^7 = 128\text{.}\)
If \(a\neq 0\text{,}\) \(\frac{a^n}{a^m} = a^{n-m}\text{.}\) For example: \(\frac{3^{5}}{3^2} = \frac{3\cdot 3\cdot 3\cdot 3\cdot 3}{3\cdot 3} = 3^3 = 27\text{.}\)
\((a^n)^m = a^{nm}\text{.}\) For example: \((2^{3})^2 = (2\cdot 2\cdot 2)\cdot(2\cdot 2\cdot 2) = 2^6 = 64\text{.}\)
\((ab)^n = a^nb^n\text{.}\) For example: \((2\cdot 3)^2 = (2\cdot 3)\cdot (2\cdot 3) = 2\cdot 2\cdot 3\cdot 3\) \(= 2^2\cdot3^2 = 36\text{.}\)
\(\left(\frac{a}{b}\right)^{n} = \frac{a^n}{b^n}\text{.}\) For example: \(\left(\frac{2}{3}\right)^2 = \frac{2}{3}\cdot\frac{2}{3} = \frac{4}{9}\text{.}\)
More subtlety arises when making sense out of zero, negative, and fractional exponents. The problem is that we don't know what it means to multiply a number by itself zero times, a negative number of times, or a fractional number of times. Because of this, we use the properties listed above to define zero, negative, and fractional exponents.
First, let's consider what \(a^0\) should equal, where \(a\) is a nonzero number. We know that if \(n\) is any number that \(0 = n-n\text{.}\) Using the second exponent property given above, we have
Since \(\frac{a^n}{a^n} = 1\text{,}\) we define \(a^0 = 1\) whenever \(a\) is not zero (\(0^0\) is undefined).
Now consider a negative exponent, \(a^{-n}\text{.}\) Here we use the first two exponent properties to arrive at what \(a^{-n}\) must be. We have
Shortening this string of equalities, we have \(a^{n}a^{-n} = 1\text{.}\) Now we divide both sides by \(a^{n}\) to get \(a^{-n} = \frac{1}{a^{n}}\text{.}\) In words, a negative exponent indicates division by the same number with a positive exponent.
Finally, let's consider what \(a^{\frac{1}{n}}\) should be. This time we'll use the third exponent property that a power raised to a power reults in the exponents being multiplied. Thus we have,
So \(a^{\frac{1}{n}}\) is the number that when raised to the \(n\)-th power results in \(a\text{.}\) This is exactly a description of the \(n\)-th root, \(\sqrt[n]{a}\text{.}\) Going slightly further with the third exponent property, we have \(a^\frac{m}{n} = \sqrt[n]{a^m} = (\sqrt[n]{a})^m\text{.}\)
Question 1.3.3.
Justify the last sentence of the last paragraph. Hint: First note that \(\frac{m}{n}\) can be written as \(m\cdot\frac{1}{n}\text{,}\) then apply property number three from 1.3.2
So in summary we have the following:
Fundamental Properties 1.3.4. Zero, Negative, and Fractional Exponents.
\(a^0 = 1\) when \(a\neq 0\text{.}\)
\(a^{-n} = \frac{1}{a^n}\text{:}\) negative exponents denote division.
\(a^{\frac{m}{n}} = \sqrt[n]{a^m} = (\sqrt[n]{a})^m\text{:}\) denominators in fractional exponents denote roots.
Question 1.3.5.
Evaluate the following without a calculator. Make sure you do it as efficiently as possible using properties of exponents.
\(4^{\frac{3}{2}}\)
\(9^{-\frac{1}{2}}\)
\((\frac{1}{27})^{-\frac{2}{3}}\)
\(\frac{1}{7^{-2}}\)
\(\frac{10^9}{10^7}\)
\(16^{\frac{5}{4}}\)
Question 1.3.6.
Use properties of exponents to write the following in a simpler way using only positive exponents.
\(-4^0\)
\(z^{-3} \cdot z^3\)
\(w^{-4} \cdot(4x)^0 \cdot x^6\)
\(\dfrac{5t^3}{t^{-6}}\)
\(\left(\dfrac{a^2}{b^3} \right)^{-1}\)
\(\left(\dfrac{x}{3} \right)^{-2}\)